EFFECT OF DIETARY SUPPLEMENTATION WITH CLOMIPHENE CITRATE ON SOME PRODUCTIVE AND PHYSIOLOGICAL TRAITS OF LAYING JAPANESE QUAIL - Hasanain N. Ezzat; R. S. Al-Mahdawi; Mohammed A. Hussein; A. S. Al-Hassani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted to evaluate the effect of supplementation different levels of Clomiphene citrate to the diet of female quail on productive and some physiological traits. The experiment was conducted in a commercial farm from 2/3/2021 to 24/5/2021 (3 months). Females aged 50 weeks (160 females) were randomly distributed into four treatments, and each treatment included four replicates (10 birds for each replicate). The treatments were divided into a control group (T1; basic diet only), second treatment (T2; basic diet + 0.25 mg / female / day), third treatment (T3; basic diet + 0.50 mg / female / day, fourth treatment (T4; basic diet + 0.75 mg / female / day Clomiphene citrate). The results of the study indicated a significant improvement in favor of the addition treatments compared with the control treatment when calculating the average (%) of eggs production, the average of eggs weight (gm), the average of eggs mass (gm/female/day), and cumulative egg number (egg/female). As for the physiological characteristics, the results shown a high concentration of calcium and phosphorous in the blood serum within the additive treatments compared with the control While there were no significant differences observed among treatments in total protein, albumin, globulin, and cholesterol. It could be conclude from this study that the addition of Clomiphene citrate to the diet improved the reproductive and physiological characteristics of female quail.